From optical spectra to phase diagrams - the binary mixture N2-CO - Vetter, M.; Brodyanski, A.; Jodl, H.-J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We investigated the T-c% phase diagram of the binary system N2-CO. From changes in IR spectra of all kinds of mode excitations (phonons, vibrons) we were able to determine the temperature of phase transitions (solid-solid, solid-liquid). The improvements in comparison to structural investigations by x-rays or electrons are the following: sample growing and handling with perfect optical and thermodynamic quality; determinationof actual concentration (N2)x(CO)y from optical spectra; reduction of thermal hysteresis bycareful cooling-heating cycles of the samples.